Spontaneous hemoperitoneum by rupture of bepatic metastasis. - Armand Ugon, Alfredo; Lyonnet, Alberto; Perdomo, Roberto (Cirugía del Uruguay, 1976)
The authors discuss two cases of spontaneóus peritoneal hemorrhage by rupture of hepatic metastasis. That is not a frequent complicatfon. In one of the cases a diagnosis of hemoperitoneum hád been previously done by paracenthesis. In both cases, the bleeding was treated with a palliative procedure: suture over "Gelfoam" in one case and packing in the other.